1986
DOI: 10.1002/prac.19863280305
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Konformation einiger Dioxaspirane mit dem Bicyclo[2.2.2]octan‐System

Abstract: Synthesis and Conformation of Some Dioxaspiranes with Bicyclo [2.2.2]octane System By condensation of 7,7‐bis‐(bromomethyl)‐2,3,5,6‐dibenzo‐bicyclo[2.2.2]octane with different diols, three new “bridge‐spiranes” 1, 2 and 3 were obtained. On the basis of 1H‐n.m.r. spectra and the respective topic relations of the hydrogen atoms the dominant conformations of heterocyclic rings in these compounds have been assigned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
1988
1988

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This resemblance pattern is expected since a higher genetic correlation between milk and protein yield, than between milk and fat. has been found when working with 305-day records [24,40]. Strabel and Misztal [95] found that fat yield heritability estimates decreased toward the middle of lactation and rose after reaching the minimum.…”
Section: Third Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This resemblance pattern is expected since a higher genetic correlation between milk and protein yield, than between milk and fat. has been found when working with 305-day records [24,40]. Strabel and Misztal [95] found that fat yield heritability estimates decreased toward the middle of lactation and rose after reaching the minimum.…”
Section: Third Approachmentioning
confidence: 99%
“…The effect of covariance component estimates on the effect of fixed factors in model (3.1) was studied by analyses of variance. A summary for the analyses of variance for fixed effects is presented in [35,36,37,39]. In the present study, the interaction of parity-calving-season-state with square root and logarithm of days-in-milk were fit to account for the general shape of the lactation curve.…”
Section: Analyses Of Variance Of Fixed Effectsmentioning
confidence: 99%
See 1 more Smart Citation